Air-stable few-layer black phosphorus phototransistor for near-infrared detection. (19th January 2017) - Na, Junhong; Park, Kichul; Kim, Jin Tae; Choi, Won Kook; Song, Yong-Won
Abstract: We have demonstrated a few-layer black phosphorus (BP) phototransistor of stable operation in ambient air environment and at near-infrared light ( λ  = 1550 nm). The air-stable electronic and optoelectronic properties of the few-layer BP phototransistor have been achieved by a proper Al2 O3 passivation. The optical identification method and qualitative and quantitative electrical characterizations of the few-layer BP phototransistor in dark state confirmed that the device performance was robust in ambient air, to further chemical treatments, and storage of more than six months. In addition, the low-frequency noise characterizations had revealed that the noise spectral density related to the sensitivity of phototransistor was reduced. Owing to the suppression of interaction between few-layer BP and adsorbates arising from the Al2 O3 passivation, a fast rise time of the few-layer BP phototransistor, less than 100 μ s, had been observed, demonstrating the intrinsic photoresponse properties of few-layer BP. The low dark current of ∼4 nA at the operation bias and the reasonable responsivity of ∼6 mA W −1 were obtained under the condition lacking adsorbates interactions. Internally, the dark current and responsivity level was tunable by changing the operation bias. Our results are close to the intrinsic properties of the few-layer BP phototransistor, implying that it can be a building block of functioned few-layer BP photodetectors.